(untitled) (Agroindustria, Sociedad y Ambiente, 2026)
The Cordia lutea flower contains a number of bioactive compounds of interest for beverage formulation. The objective of this study was to evaluate the antioxidant, physicochemical, and toxicological properties of an infusion of dehydrated Cordia lutea flower. A completely randomized design was used, and four different treatments were formulated (0.5 g, 1.0 g, 1.5 g, and 2.0 g of dehydrated Cordia lutea CLD). The heavy metal content of the CLD sample was evaluated, and the physicochemical properties, antioxidant activity, total phenols, and microbiological quality of the infusions were characterized using a Tukey test at the 0.05% significance level. The CLD showed low cadmium (<0.04 mg/kg) and lead (0.07 mg/kg) content. The infusions presented pH levels of 5.82 ± 0.10 to 5.94 ± 0.02. absence of viscosity, turbidity: 9.43 ± 1.12 – 38.37 ± 6.62 NTU; L*: 81.63 ± 0.73 – 96.5 ± 0.36; a*: -8.43 ± 0.96 - -0.30 ± 0.81; b*: 28.23 ± 2.86 – 38.57 ± 4.33; antioxidants DPPH 304.4 ± 62.5 and ABTS 421.1 ± 91.0 μmol Trolox Equivalent/ 100 mL; Total phenols 33.25 ± 4.92 – 89.25 ± 5.74 Gallic Acid Equivalent/100mL and absence of pathogens (Salmonella, Clostridium, E. coli). T4 is considered the best treatment in terms of functionality; all infusions met the requirements established in the NTE INEN 2392 standard. Given the low toxicological load in the plant material and the presence of antioxidants in the Cordia lutea flower infusion, this beverage can be used at the agro-industrial level as a potential functional food.